Model Checking Systems with Replicated Components using CSP - Mazur, T (2011)
The Parameterised Model Checking Problem asks whether an implementation Impl(t) satisfies a specification Spec(t) for all instantiations of parameter t. In general, t can determine numerous entities: the number of processes used in a network, the type of data, the capacities of buffers, etc. The main theme of this thesis is automation of uniform verification of a subclass of PMCP with the parameter of the first kind, using techniques based on counter abstraction. Counter abstraction works by counting how many, rather than which, node processes are in a given state: for nodes with k local states, an abstract state (c(1), ..., c(k)) models a global state where c(i) processes are in the i-th state. We then use a threshold function z to cap the values of each counter. If for some i, counter c(i) reaches its threshold, z(i) , then this is interpreted as there being z(i) or more nodes in the i-th state. The addition of thresholds makes abstract models independent of the instantiation of the parameter. We adapt standard counter abstraction techniques to concurrent reactive systems modelled using the CSP process algebra. We demonstrate how to produce abstract models of systems that do not use node identifiers (i.e. where all nodes are indistinguishable). Every such abstraction is, by construction, refined by all instantiations of the implementation. If the abstract model satisfies the specification, then a positive answer to the particular uniform verification problem can be deduced. We show that by adding node identifiers we make the uniform verification problem undecidable. We demonstrate a sound abstraction method that extends standard counter abstraction techniques to systems that make full use of node identifiers (in specifications and implementations). However, on its own, the method is not enough to give the answer to verification problems for all parameter instantiations. This issue has led us to the development of a type reduction theory, which, for a given verification problem, establishes a function phi that maps all (sufficiently large) instantiations T of the parameter to some fixed type T and allows us to deduce that if Spec(T) is refined by phi(Impl(T)), then Spec(T) is refined by Impl(T). We can then combine this with our extended counter abstraction techniques and conclude that if the abstract model satisfies Spec(T), then the answer to the uniform verification problem is positive. We develop a symbolic operational semantics for CSP processes that satisfy certain normality requirements and we provide a set of translation rules that allow us to concretise symbolic transition graphs. The type reduction theory relies heavily on these results. One of the main advantages of our symbolic operational semantics and the type reduction theory is their generality, which makes them applicable in other settings and allows the theory to be combined with abstraction methods other than those used in this thesis. Finally, we present TomCAT, a tool that automates the construction of counter abstraction models and we demonstrate how our results apply in practice.